Effect of boiling methods on the nutritional profile, phytochemicals, functional properties, lipid quality and consumer acceptability of African walnut (Tetracarpidium conophorum) - Alawode, Oluwatoyin; Olatunji, Imosi; Abioye, Victoria F; Ayansola, Jumoke H; Odedeji , Joshua O (Bangladesh Journal of Scientific and Industrial Research, 2025)
This study evaluated the effects of different boiling methods on the nutritional composition, phytochemicals, functional properties, and lipid quality of African walnut (Tetracarpidium conophorum). Fresh walnuts were subjected to boiling treatments with or without shells at 100°C for 30 and 60 minutes. Boiling significantly reduced protein content but increased crude fiber and ash content, suggesting improved mineral availability and shelf life. Amino acid analysis indicated glutamic acid and aspartic acid as predominant, with essential amino acids like leucine and lysine confirming good protein quality. Boiled samples exhibited enhanced antioxidant activity and reduced levels of phytates and tannins, improving nutrient bioavailability. Lipid quality analysis indicated increased oxidative stability but reduced unsaturation in boiled walnuts. These findings demonstrate that appropriate boiling techniques can improve the nutritional and functional attributes of African walnuts, supporting their potential use as valuable functional food ingredients. Bangladesh J. Sci. Ind. Res. 60(3), 143-158, 2025